Cenovno predatorstvo v Sloveniji: pravno razlogovanje v perspektivi naziranj Komisije in Sodišča EU - Rozman, Til (LeXonomica, 2012)
Predatory Pricing in Slovenia: A Legal Reasoning with regard to the EU Commission’s and Court’s Notions. The paper analyzes chronologically the last and most important decision of the Slovenian Competition Protection Office, that deals with predatory pricing, especially in the perspective of the regulatory frameworks of both the EU and the Republic of Slovenia and in the practice of the EU Commission and the Court. It is found that the analyzed decision is consistent with the latest concepts and reasoning about predatory pricing in the EU, although still emphasizes predatory intent instead of anti-competitive effects. As a conclusion it is argued that there are substantial differences and discrepancy in the terminology within the Slovene jurisprudence, translated relevant documents and case law. Cenovno predatorstvo v Sloveniji: pravno razlogovanje v perspektivi naziranjKomisije in Sodišča EU. Prispevek analizira kronološko zadnjo in doslej najpomembnejšo odločbo Urada RS za varstvo konkurence, ki obravnava cenovno predatostvo, in sicer v perspektivi normativnega okvira v Republiki Sloveniji in Evropski uniji ter praksi Komisije in Sodišča EU. Avtor ugotavlja, da odločba sledi novejšim konceptom in naziranjem o cenovnem predatorstvu v EU, vendar še vedno poudarja ugotavljanje izključitvenega namena namesto protikonkurenčnih učinkov. Avtor ugotavlja tudi precejšna terminološka razhajanja v teoriji inneskladja s slovenskimi prevodi relevantnih dokumentov in sodne prakse.